2013
DOI: 10.1002/bio.2610
|View full text |Cite
|
Sign up to set email alerts
|

Study on the binding of chlorogenic acid to pepsin by spectral and molecular docking

Abstract: The interaction of pepsin with chlorogenic acid (CHA) was investigated using fluorescence, UV/vis spectroscopy and molecular modeling methods. Stern-Volmer analysis indicated that the fluorescence quenching of pepsin by CHA resulted from a static mechanism, and the binding constant was 1.1846 × 10(5) and 1.1587 × 10(5) L/mol at 288 and 310 K, respectively. The distance between donor (pepsin) and acceptor (CHA) was calculated to be 2.39 nm and the number of binding sites for CHA binding on pepsin was ~ 1. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…in the binding between NIC and pepsin. Results from the present study and other reports showed that binding of many small molecules pepsin occurred via a static quenching mechanism [7,10,11,[36][37][38]. Notably, Li Zhen et al studied the binding between pepsin and nucleoside analogs (FNC, CYD, and CMP) via a static quenching mechanism.…”
Section: The Pattern Of Interaction Forcesupporting
confidence: 53%
See 1 more Smart Citation
“…in the binding between NIC and pepsin. Results from the present study and other reports showed that binding of many small molecules pepsin occurred via a static quenching mechanism [7,10,11,[36][37][38]. Notably, Li Zhen et al studied the binding between pepsin and nucleoside analogs (FNC, CYD, and CMP) via a static quenching mechanism.…”
Section: The Pattern Of Interaction Forcesupporting
confidence: 53%
“…Curcumin [7] binding with pepsin mainly through hydrophobic interactions with one binding site, while pepsin bind with silybin [10], and nobilietin [37] mainly through hydrophobic and electrostatic interactions. Chlorogenic acid [38] and pepsin were mainly strengthened by Van der Waals' forces and hydrogen bonds. Furthermore, the binding affinity or binding constants varied.…”
Section: The Pattern Of Interaction Forcementioning
confidence: 99%
“…3D fluorescence spectroscopy has been widely used in fluorescence analysis in recent years because it can provide detailed information of the conformational and microenvironmental changes of proteins combining with small molecules . Figure (c, d) shows the 3D fluorescence spectra of pepsin alone and in complex with AR14, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For macromolecules, fluorescence measurements can provide some information on the binding of small molecules with protein, such as the binding mechanism, binding mode, binding constants, binding sites, and intermolecular distances. A variety of molecular interactions can result in quenching, including excited state reactions, molecular rearrangements, energy transfer, and ground-state complex formation [15,16]. Fluorescence-quenching mechanisms generally include static and dynamic quenching [17].…”
Section: Interaction Mechanism Between Hsa and Norgestrelmentioning
confidence: 99%